Treatment Effects of Removable Functional Appliances in Pre-Pubertal and Pubertal Class II Patients: A Systematic Review and Meta-Analysis of Controlled Studies. - Giuseppe Perinetti; Jasmina Primožič; Lorenzo Franchi; Luca Contardo (PLoS ONE)
Background Treatment effects of removable functional appliances in Class II malocclusion patients according to the pre-pubertal or pubertal growth phase has yet to be clarified. Objectives To assess and compare skeletal and dentoalveolar effects of removable functional appliances in Class II malocclusion treatment between pre-pubertal and pubertal patients. Search methods Literature survey using the Medline, SCOPUS, LILACS and SciELO databases, the Cochrane Library from inception to May 31, 2015. A manual search was also performed. Selection criteria Randomised (RCTs) or controlled clinical trials with a matched untreated control group. No restrictions were set regarding the type of removable appliance whenever used alone. Data collection and analysis For the meta-analysis, cephalometric parameters on the supplementary mandibular growth were the main outcomes, with other cephalometric parameters considered as secondary outcomes. Risk of bias in individual and across studies were evaluated along with sensitivity analysis for low quality studies. Mean differences and 95% confidence intervals for annualised changes were computed according to a random model. Differences between pre-pubertal and pubertal patients were assessed by subgroup analyses. GRADE assessment was performed for the main outcomes. Results Twelve articles (but only 3 RCTs) were included accounting for 8 pre-pubertal and 7 pubertal groups. Overall supplementary total mandibular length and mandibular ramus height were 0.95 mm (0.38, 1.51) and 0.00 mm (-0.52, 0.53) for pre-pubertal patients and 2.91 mm (2.04, 3.79) and 2.18 mm (1.51, 2.86) for pubertal patients, respectively. The subgroup difference was significant for both parameters (p<0.001). No maxillary growth restrain or increase in facial divergence was seen in either subgroup. The GRADE assessment was low for the pre-pubertal patients, and generally moderate for the pubertal patients. Conclusions Taking into account the limited quality and heterogeneity of the included studies, functional treatment by removable appliances may be effective in treating Class II malocclusion with clinically relevant skeletal effects if performed during the pubertal growth phase.